Transmission of Human Papilloma virus among couples: concordância entre os subtipos e sítios diferentes de infecção - Agnaldo Lopes da; Andréa Gazzinelli; Carlos Eduardo Gazzinelli; Eduardo Batista; Soraya Moukhaiber (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Among the sexually transmitted diseases, the highest world incidence is infection by the human papillomavirus (HPV). It affects 65% of men and 80% of women. At the moment, it is only the viral infection associated with development of cancer. Objective: To review the aspects related to the transmission of the HPV in men and women, collecting studies that analyze their transmission among couples, comparing the correlation between the partners and the transmission rates among different sites. Methods: The study was designed based upon literature review, using medical search tools like Pubmed/Medline, with the keywords: “Human Papillomavirus”; and combinations, “Human Papillomavirus” and “couples,” “HPV infection in men,” “transmission of papilloma virus.” The studies selected were those that included HPV detection through HPV-DNA. Results: The concomitance of at least one viral genotype between genders showed great variation from 2.63 to 100%, the latter being specifically related to high-grade and consistency in HIV-positive groups. Conclusion: Men play a decisive role in this mechanism, both as a transmitter and as a carrier, thus they should also be the focus of HPV vaccination and treatment policies